The Effect of Inquiry Model on Teachers Self Controlling in Class X Virus in SMA Private Vocational School UISU Medan - Aida, Zul (International Journal for Educational and Vocational Studies, 2020)
This study aims to determine the effect of the Inquiry learning model on student learning outcomes in class X virus material in UISU Medan Private High School. The research method uses descriptive research methods and types of correlational research to see if there is an effect of using the inquiry model on self-controlling teachers with a research sample of 2 classes that were randomly assigned using cluster random sampling technique. In class X-1 they are taught the guided inquiry learning model, and class X-2 is taught using the conventional learning model. The instrument used in this study was a test of critical thinking skills in the form of a written test. The data analysis technique uses correlation regression. Based on the calculation, it is found that there is an influence in the use of the Inquiry Model on Teacher Self-Controlling with a value of r = 0.43, in the value of Covariate Analysis using SPSS, namely 55.20 ± 15.65, which is significantly greater than the class control that is equal to 50.10 ± 11.44. The results of the analysis show that there is a significant influence in the use of the Inquiry model on Teacher Self-Controlling at the real level Î± = 0.05.